Radiofrequency ablation of liver cancers adjacent to the gallbladder without gallbladder isolation under contrast-enhanced ultrasound monitoring: a preliminary study. (1st January 2019) - Long, Yinglin; Yan, Ronghua; Li, Kai; Luo, Liping; Zeng, Qingjing; Tan, Lei; Zhang, Man; Zheng, Rongqin; Xu, Erjiao
Abstract: Purpose: The purpose of this study was to investigate the feasibility, safety and efficacy of intra-procedural contrast-enhanced ultrasound (CEUS) monitoring of the radiofrequency ablation (RFA) of liver cancers adjacent to gallbladder (GB) without GB isolation. Materials and methods: From May 2016 to July 2017, patients with liver cancers adjacent to GB (≤10 mm) who intended to undergo ultrasound-guided RFA without GB isolation in our hospital were prospectively enrolled. During the RFA procedures, CEUS was employed to evaluate the therapeutic response and the perfusion of the intact GB wall. The outcomes of GB and liver cancers were followed up and recorded. Results: 23 patients (18 male, 5 female) with 23 liver cancers (mean 18 mm, range 8–34 mm) adjacent to GB were enrolled. There were 12 tumors that abutted the GB while 11 tumors located within 10 mm of the GB. After the RFA procedures, intra-procedural CEUS evaluation demonstrated the perfusion of the GB wall was intact in all 23 patients and technical success rate of RFA was 100% (23/23). According to the contrast-enhanced CT/MR one month after RFA, the technical efficacy rate was 100% (23/23). During the follow-up period (range: 12–23 months, median: 17 months), no local tumor progression occurred and no major complications arised. Overall survival at 1-year was 100%. Thickening of GB wall was detected in 11 patients. The thickness of GB wall returned to the pre-ablation level in five patients. Conclusion: CEUS-monitored RFA of liver cancers adjacent to GB without GB isolation was feasible, safe and effective.